Penggunaan Model Problem Based Learning (PBL) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Rismawanti Putri (Lembaga Bale Literasi, 2025)
The Problem-Based Learning (PBL) model was implemented with 12 fifth-grade students (6 boys, 6 girls) to enhance critical thinking skills in understanding the